Aortoesophageal fistula following thoracic branch endoprosthesis for cryptogenic penetrating aortic ulcer in a patient on pembrolizumab - Sarah Kim, BA; Patrick D. Conroy, MD; Mark Zemela, MD; Bruce L. Tjaden, Jr., MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Penetrating aortic ulcers are uncommon and life-threatening. We describe the case of a 67-year-old man who presented with fever and chills and was found on computed tomographic scan to have a thoracic penetrating aortic ulcer. The patient underwent placement of a thoracic branch endoprosthesis, with a postoperative course complicated by ileocolic pseudoaneurysm, progressive aortitis, and a fatal aortoesophageal fistula. The management of penetrating aortic ulcer in the setting of multiple confounding factors is discussed in the context of this patient’s complex medical presentation, with a focus on the potential role of pembrolizumab in his disease progression.